CT Scan Study of Third Ventricles Dimensions in Normal Population - Sarfraz Ahmed, Muhammad Nauman Akram, Amir Hussain Ashraf, Amina Noor, Faiza Irshad, Mufassar Nishat, (Pakistan Journal of Medical & Health Sciences, 2023)
The human brain is not only one of the most important organs in the human body, but it is also one of the most convoluted and is still not fully understood.As the process of aging continues, the brain goes through a number of changes as a whole, including both physical and histological shifts Study Design: Research utilizing a cross-sectional prospective study design Study Duration: January 2021 and continuing through November 2021. Place of Study: Allama Iqbal memorial teaching hospital khawaja Muhammad safdar medical college Sialkot Methodology: The participants in the study were given a standardized questionnaire to complete, in addition to a variety of checklists, in order to complete their assessments. The data was transferred over to SPSS version 23 for additional analysis. In order to investigate the nature of the connection that exists between age and gender, in addition to the height and diameter of the third ventricle, we turned to Pearson's product-moment correlation coefficient. Result: The analysis of variance (ANOVA), which calculates the mean difference between age groups, was performed. The p-value needs to be lower than 0.05 in order for the experiment to be considered statistically significant. The mean height of the third ventricle in males was 13.57 millimeters and the mean height in females was 13.52 millimeters. The mean diameter of the third ventricle in males was 2.98 millimeters and the mean diameter in females was 2.56 millimeters. When the size of the third ventricle in males was compared to that of the third ventricle in females, it was discovered that the size of the third ventricle in males is greater than that of the third ventricle in females. Keywords: CT Scan, ventricles dimensions, hydrocephalus, schizophrenia, psychotic disorders